Implementasi Peraturan Pemerintah Nomor 31 Tahun 2021 dan Nomor 27 Tahun 2021 dalam Penerbitan Sertifikat Kelaikan Kapal Perikanan di Pelabuhan Sorong - AB Zulfiqar; Wiwik Sri Widiarty; Aartje Tehupeiori (Syntax Idea)
This academic article aims to analyze the implementation of Government Regulation (GR) Number 31 of 2021 and GR Number 27 of 2021 in the issuance of certificates of fitness for fishing vessels at the Sorong Port in Indonesia. These regulations set the requirements and procedures related to certificates of fitness for fishing vessels, which are crucial for ensuring the safety and sustainability of the fishing industry in the region. This research documents how these government regulations are applied at the Sorong Port, identifies potential challenges that may arise in the certificate of fitness issuance process, and evaluates the effectiveness of law enforcement and oversight by relevant authorities. The study discusses the legal framework governing certificates of fitness for fishing vessels, including provisions related to safety standards, environmental protection, and other technical requirements that fishing vessels must comply with. Additionally, the article highlights common issues that arise in the practice of issuing certificates of fitness, such as meeting technical requirements and vessel fitness, as well as bureaucratic process-related problems. In this analysis, the impact of legal regulations on the practice of issuing certificates of fitness at the Sorong Port will be considered, as well as the role and effectiveness of oversight by authorities in ensuring that fishing vessels comply with applicable regulations. The research findings indicate the need for improvements in the implementation and enforcement of government regulations related to certificates of fitness for fishing vessels at the Sorong Port, Indonesia. This article contributes to a deeper understanding of the legal framework governing certificates of fitness for fishing vessels and promotes improvements in regulations and safer, more sustainable fishing industry practices.